Catatan Pendidikan Indonesia: Evaluasi, Solusi, & Ekspektasi - Siva Aprilyanti; Masduki Asbari; Alfiana Supriyanti; Ica Alfiatun Fadilah (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this discussion is to evaluate the opportunities and potential of education in Indonesia in the future. So that we can achieve optimal learning outcomes and not be left behind by other countries, contributions from the community and government are really needed for Indonesian education. This research report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from the Satu Persen - Indonesian Life School Youtube channel entitled "Indonesian Education Notes: Evaluation, Solutions & Expectations" which he delivered. The program aims to show concern for the nation's children towards education in Indonesia which is lagging behind other countries. The speaker identified three main problems in the current condition of Indonesian education, namely inadequate infrastructure, low quality teachers, and lack of integration with nationalist values. he also emphasized the importance of making education more inclusive and accessible to all Indonesian children, regardless of background.